2018
DOI: 10.1101/337782
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The non-transcranial TMS-evoked potential is an inherent source of ambiguity in TMS-EEG studies

Abstract: 7Tel: +45 3862 6541; Email: hartwig.siebner@drcmr.dk; http://www.drcmr.dk/siebner 2 8All rights reserved. No reuse allowed without permission.was not peer-reviewed) is the author/funder, who has granted bioRxiv a license to display the preprint in perpetuity.The copyright holder for this preprint (which . http://dx.doi.org/10.1101/337782 doi: bioRxiv preprint first posted online Jun. 4, 2018; 2 Abstract (246 words) 2 9Transcranial Magnetic Stimulation (TMS) excites populations of neurons in the stimulated c… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
93
3
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(104 citation statements)
references
References 70 publications
7
93
3
1
Order By: Relevance
“…When considering that TMS‐EEG is approaching clinical translation, it must be taken into account that the TMS pulse can induce unwanted somatosensory responses that have an impact on the cortical signal detected with EEG . An online TEP quality control during data collection will be crucial to obtain high‐quality and genuine TMS‐evoked brain responses.…”
Section: Discussionmentioning
confidence: 99%
“…When considering that TMS‐EEG is approaching clinical translation, it must be taken into account that the TMS pulse can induce unwanted somatosensory responses that have an impact on the cortical signal detected with EEG . An online TEP quality control during data collection will be crucial to obtain high‐quality and genuine TMS‐evoked brain responses.…”
Section: Discussionmentioning
confidence: 99%
“…Other technical constraints should also be noted. A recent study has suggested that some of the TMS-evoked response may be driven by sensory stimulation rather than just direct cortical perturbation 49 . Given that the same stimulation parameters were used in both the wake and disconnected/conscious states it is likely that the relative contribution of transcranial and sensory responses was constant across the states.…”
Section: Discussionmentioning
confidence: 99%
“…Yet, the most important challenge will be to develop truly closed-loop BSDBS (Figure 1B ) that allows to continuously monitor the brain signals of interest, while concurrently applying NIBS to achieve and maintain the desired brain state and to control perception or behavior. The successful real-time removal of TMS/TCS stimulation artifacts (Walter et al, 2012 ; Herring et al, 2015 ; Rogasch et al, 2017 ) and EEG correlates of multisensory co-stimulation during TMS (Herring et al, 2015 ; Conde et al, in press ) and TCS (Schutter, 2016 ; Herring et al, 2018 ) is therefore a core developmental goal for the near future.…”
Section: Challenges and Future Perspectives For Bsdbsmentioning
confidence: 99%